Analisis Modalitas Tuturan Basuki Cahaya Purnama dalam Wacana Kalijodo - Yusep Ahmadi F. (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2016)
This paper discusses speech modality uttered by the Governor of Jakarta Basuki Cahaya Purnama on Kalijodo discourse. The problem in this research is the form of speech modality, attitude, and representation of Jakarta Governor, Basuki Cahaya Purnama, on Kalijodo discourse. This research applies the theory of modality from Alwi (1992) and Fairclough (Santoso, 2012). The method used in this research is qualitative-descriptive method, by presenting and assessing the exposures of linguistic data through modality theory as a device analysis. The analysis shows there are nine forms of deontic modalities with command significancy and/or nine forms of relational-command modalities. The aggregate of such modality is more dominant than the amount of epistemic modality with certainty meaning as many as four, one modality of dynamic ability, one modality of predictability epistemic, and one modality of intentional demand. This represents that Basuki Cahaya Purnama’s attitude is very powerful. in addition, the findings of deontic-command modality or dominant command-relational epistemic modality coupled with modality of certainty epistemic in the second place indicates that Basuki Cahaya Purnama in tackling the case of Kalijodo, he applied a strict instructions approach without any doubt.